Philosemitism under a Darkening Sky: Judaism in the French Catholic Revival (1900–45) - Moore, Brenna (The catholic historical review, 2013)
The work of Charles Péguy (1873–1914), Léon Bloy (1846–1917), and especially Raïssa Maritain (1883–1960) provides insight regarding the relationship between French Jews and Catholics in the early-twentieth century. The author argues that these writers sought an alternative to both the secular laïcité respect for Jews that depended on suppressing Jewish particularity as a prelude to citizenship and the classic Christian contempt of Judaism. They created a highly aesthetic and imaginative philosemitic alternative that advocated the unity between Jews and Christians, and occasionally supported resistance to antisemitism. Yet these thinkers also employed essentialized images, emphasizing Jewish suffering and advocated, in some cases, conversions to Christianity.